Exploring human factors in the operating room: scoping review of training offerings for healthcare professionals. Issue 2 (29th March 2022) - Lee, Alex; Finstad, Alexandra; Tipney, Ben; Lamb, Tyler; Rahman, Alvi; Devenny, Kirsten; Abou Khalil, Jad; Kuziemsky, Craig; Balaa, Fady
Abstract: Background: Human factors (HF) integration can improve patient safety in the operating room (OR), but the depth of current knowledge remains unknown. This study aimed to explore the content of HF training for the operative environment. Methods: We searched six bibliographic databases for studies describing HF interventions for the OR. Skills taught were classified using the Chartered Institute of Ergonomics and Human Factors (CIEHF) framework, consisting of 67 knowledge areas belonging to five categories: psychology; people and systems; methods and tools; anatomy and physiology; and work environment. Results: Of 1851 results, 28 studies were included, representing 27 unique interventions. HF training was mostly delivered to interdisciplinary groups ( n = 19; 70 per cent) of surgeons ( n = 16; 59 per cent), nurses ( n = 15; 56 per cent), and postgraduate surgical trainees ( n = 11; 41 per cent). Interactive methods (multimedia, simulation) were used for teaching in all studies. Of the CIEHF knowledge areas, all 27 interventions taught 'behaviours and attitudes' (psychology) and 'team work' (people and systems). Other skills included 'communication' ( n = 25; 93 per cent), 'situation awareness' ( n = 23; 85 per cent), and 'leadership' ( n = 20; 74 per cent). Anatomy and physiology were taught by one intervention, while none taught knowledge areas under work environment. Conclusion: Expanding HF education requires a broader inclusion of the entirety of sociotechnical factors such as contributions of the work environment, technology, and broader organizational culture on OR safety to a wider range of stakeholders. Abstract : To examine the scope of application of human factors for the operating room, this study explored the content of emphasis in human factors education to date. We found that human factors training is limited to teaching behavioural, non-technical skills but may not address the entirety of sociotechnical factors that impact operating room safety. There is room to expand the range and scope of human factors for the operating room in future curricula to include contributions of the work environment, technology, and broader organizational culture on safety to a wider range of stakeholders.